Factors influencing knowledge and performance of selfcare practices among type 2 diabetes mellitus patients in a teaching hospital in Nigeria - Oluwaseun O Abiodun; Timothy Aghogho Ehwarieme; Otowve Agofure (Academy Publishing Center, 2024)
Background: There are several factors that influence the levels of knowledge and performance of self-care practices (SCP) among patients with Type 2 Diabetes Mellitus (T2DM) in different parts of the world. The objective of the study was to identify the factors that influence the levels of knowledge and performance of self-care practices among patients with T2DM in a Teaching Hospital. Material and Methods: The study utilized a descriptive cross-sectional design. It was carried out in a tertiary health facility in Ondo State, Nigeria. 132 Participants who were T2DM patients attending endocrine clinic at the hospital were selected for the study using convenience sampling. A structured questionnaire and a self-care performance recall form were used for data collection. Data collected were analyze using descriptive while the hypothesis was done using Binary Logistics Regression at a 0.05% significant level. Results: Results revealed that an individual's belief in innate ability (OR=2.871) and self-efficacy (OR=2.121) were twice more likely to have been more associated with increased level of knowledge of self-care practice. Also, beliefs and attitude about life (OR=2.533) and knowledge of the disease process and severity (OR=2.706) were twice more likely to have been more associated with better performance of SCP. Conclusion: There were poor knowledge of self-care practices and its performance among the participants, factors that were more associated with increased levels of knowledge and performance of SCP as reported in the study should be strengthened as they positively impact outcomes in patients with T2DM.   Received: 01 March 2024 Accepted: 06 April 2024 Published: 08 May 2024